Effect of Green Human Resource Management (GHRM) and Green Work Engagement on Employee Performance: Evidence from PERUMDA Tirta Mangkaluku, Palopo City - Putri Putri; Muhammad Kasran; I Ketut Patra (BIMA Journal (Business, Management, & Accounting Journal), 2026)
Purpose: This study aims to determine how employee performance at PERUMDA Tirta Mangkaluku Kota Palopo is influenced by GHRM and Green Work Engagement (GWE). Methodology: This study uses a quantitative approach by collecting data through questionnaires. They involved 76 employees and used a basic random selection method. The data were analysed using SPSS version 24 and Multiple Linear Regression Analysis. Results: The results show that employee performance is positively and significantly influenced by GHRM and GWE. Findings: The study shows that Green Human Resource Management and Green Work Engagement both have a positive and important impact on how well employees perform. Partially, GHRM has been shown to boost employee performance, just like GWE has. At the same time, both variables strongly affect how well employees perform. The coefficient of determination, or R², is 0.757, which means that 75.7% of the changes in employee performance can be explained by GHRM and GWE. Novelty: This study shows that Green Work Engagement really makes a difference in how well employees perform, which is different from Mering (2024), who said that Green Work Engagement doesn't have much impact on employee performance. Originality: This study adds real evidence by looking at how GHRM and GWE affect regional companies (PERUMDA), which hasn't been widely studied before. This study also helps show how using HR practices that focus on the environment connects to employees' willingness to work in a green way, which in turn affects their performance, especially in the public service sector. Conclusions: The study concludes that organizations should prioritize both GHRM implementation and the cultivation of green work engagement to optimize employee performance outcomes. Type of Paper: This paper is an empirical research paper.